Pioneering the Establishment of Waste Banks as a Form of Community Empowerment - Novela Juliana; Paul Arjanto (DEVOTIONIS, 2024)
The purpose of this community service activity is to socialize the making of garbage banks in increasing public awareness of the importance of not littering. In addition, the garbage bank is useful for all the people of Labuang village so that they do not throw garbage or burn rubbish, because the rubbish can generate money, crafts, etc., so that it can boost the economy of the people in Labuang village. The method of implementing the activity is carried out through socialization and assistance to the community of Kodangbang village, Namrole District, Buru Selatan Regency. The "LOLIK LALEN FEDAK FENA" Trash Bank socialization activity in Labuang Village, the community can also find out how to manage waste into economic value goods. Garbage, which has so far been only underestimated by the general public, is that rubbish is something that creates an unpleasant, dirty and disgusting odor. But with the socialization of waste management, smelly and dirty garbage, if managed properly, can be of economic value as currently done by one of the garbage banks, the "LOLIK LALEN FEDAK FENA" Garbage Bank in Labuang Village.